Faktor pendorong motivasi orang tua merawatkan gigi anak di klinik Fakultas Kedokteran Gigi Unair (Stimulating factor of parents' motivation to take their children's dental health for treatment in the Faculty of Dentistry Airlangga University) - Dita Anggriana; Musyrifah Musyrifah (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
Children dental health is very beneficial for children's growth Parent’s motivation for taking their children dental for treatment before more serious dental damage can help to decrease the prevalence of children's dental damage, especially for patients who came to pedodontia clinic in the faculty of Dentistry Airlangga University. This study aimed to know the parents' motivation to take their children dental for treatment in Pedodontia clinic in the faculty of Dentistry Airlangga University by giving questionnaire to 42 patient’s parents. The result of this study suggested that clinic’s facilities (scored: 2.86) as the stimulating factor had the biggest influence in motivating patient’s parents.